Rice Homeodomain Protein WOX11 Recruits a Histone Acetyltransferase Complex to Establish Programs of Cell Proliferation of Crown Root Meristem. Issue 5 (9th May 2017) - Zhou, Shaoli; Jiang, Wei; Long, Fei; Cheng, Saifeng; Yang, Wenjing; Zhao, Yu; Zhou, Dao-Xiu
Abstract : Rice WOX11 promotes crown root development by interacting with a histone acetylation complex to induce permissive chromatin of gene expression. Abstract: Shoot-borne crown roots are the major root system in cereals. Previous work has shown that the Wuschel-related homeobox gene WOX11 is necessary and sufficient to promote rice ( Oryza sativa ) crown root emergence and elongation. Here, we show that WOX11 recruits the ADA2-GCN5 histone acetyltransferase module to activate downstream target genes in crown root meristem. Rice ADA2 and GCN5 genes are highly expressed in root meristem and are shown to be essential for cell division and growth. WOX11 and ADA2-GCN5 commonly target and regulate a set of root-specific genes involved in energy metabolism, cell wall biosynthesis, and hormone response, some of which are known to be important for root development. The results indicate that the recruitment of ADA2-GCN5 by WOX11 establishes gene expression programs of crown root meristem cell division and suggest that permissive chromatin modification involving histone acetylation is a strategy for WOX11 to stimulate root meristem development.